On the Solution of a Locally Finite System of Linear Inequalities with Graph Structure - Ostapenko, V. V.; Finin, G. S. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We propose a method for the solution of a locally finite system of linear inequalities that arises in the course of solution of problems of control over resource in networks with generalized Kirchhoff law. We present a criterion for a system of inequalities to have the graph structure.